Simple English Learning for Rural Elementary Students: A Community Service in Subur Village - Al-Farizy, M. Kevin; Sadri, Idris; Harahap, Siti; Zafirah, Talitha; Siregar, Nur Fadiah Arifah; Aulia, Dinda Sabda; Siregar, Nuri Handayani; Khanis, Muhammad Ilham; Zanah, Siti Nur; Wulandari, Windi; Hakim, Widiya Mentari (MUDABBIR Journal Research and Education Studies, 2025)
This community service program, titled “Simple English Learning for Rural Elementary Students: A Community Service in Subur Village,” was conducted to support early English education among elementary school children in rural areas with limited access to language learning resources. Through interactive methods such as games, songs, storytelling, vocabulary posters, and hands-on projects, the program aimed to enhance students’ engagement, motivation, and basic English skills. The program also included Qur’an reading sessions and basic literacy support to strengthen the children’s overall educational foundation. The results showed a positive response from the students, who were enthusiastic and actively involved throughout the activities. The integration of microteaching and artefact creation further enriched both student learning and the teaching experience of the facilitators. This initiative proves that simple, joyful, and culturally responsive approaches can significantly improve language learning outcomes for rural students and foster essential competencies for their future development.